Exploration of perfluorooctane sulfonate degradation properties and mechanism via electron-transfer dominated radical process. (15th May 2022) - Li, Meng; Jin, Yu-Ting; Yan, Jian-Fang; Liu, Zhang; Feng, Nai-Xian; Han, Wei; Huang, Long-Wei; Li, Qin-Ke; Yeung, King-Lun; Zhou, Shao-Qi; Mo, Ce-Hui
Highlights: PFOS degradation can keep a high level by electrochemical oxidation. Electrochemical oxidation was effective to multiple organic contaminants. DFT calculations confirmed electron can be transferred from PFOS to PMS. Ti4O7 could serve as the conductive bridge to promote the electron transfer. The ultrasonic treatment can effectively active electrode for PFOS degradation. Abstract: Polyfluoroalkyl and perfluoroalkyl chemicals (PFCs) widely used in lubricants, surfactant, textiles, paper coatings, cosmetics, and fire-fighting foams can release a large deal of organics contaminants into wastewater and pose great risks to the health of humans and eco-environments. Although advanced oxidation processes can effectively deconstruct various organic contaminants via reactive radicals, the stable structure of PFCs makes it difficult to be degraded. Here, we confirm that electrochemical oxidation process coupled with peroxymonosulfate (PMS) reaction can efficiently destroy stable structure of PFCs via electron transfer and meanwhile completely degrade PFCs via generated active radicals. We further studies via capturing and scavenging radicals, and DFT calculations find that electron hydroxyl radials play a dominant role in degrading PFCs. Based on the calculations of adsorption energy and molecular orbital energy we further demonstrate that many active sites on the surface of Ti4 O7 (1 0 4) plane can rapidly take part in electrochemical reaction for generating radials and removing organic contaminants. These results give a promising insight towards high-effective and deep degradation of PFCs via electrochemical reaction coupled with advanced oxidation processes, as well as providing guidance and technical support for the remove of multiple organic contaminants. Graphical abstract: Image, graphical abstract